2016
DOI: 10.1093/dnares/dsw027
|View full text |Cite
|
Sign up to set email alerts
|

Discrepancy among the synonymous codons with respect to their selection as optimal codon in bacteria

Abstract: The different triplets encoding the same amino acid, termed as synonymous codons, are not equally abundant in a genome. Factors such as G + C% and tRNA are known to influence their abundance in a genome. However, the order of the nucleotide in each codon per se might also be another factor impacting on its abundance values. Of the synonymous codons for specific amino acids, some are preferentially used in the high expression genes that are referred to as the ‘optimal codons’ (OCs). In this study, we compared O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 66 publications
(73 reference statements)
0
12
0
Order By: Relevance
“…However, it is now widely accepted that the codon usage bias widely differs among amino acids (Satapathy et al . ), and therefore, it would be appropriate to calculate contributions toward Ntrue^c value for different amino acids separately as given in Eqn . With this modification, Ntrue^c value may fall below 20.0 when some of the amino acids are absent in a coding sequence.…”
Section: Resultsmentioning
confidence: 99%
“…However, it is now widely accepted that the codon usage bias widely differs among amino acids (Satapathy et al . ), and therefore, it would be appropriate to calculate contributions toward Ntrue^c value for different amino acids separately as given in Eqn . With this modification, Ntrue^c value may fall below 20.0 when some of the amino acids are absent in a coding sequence.…”
Section: Resultsmentioning
confidence: 99%
“…However, the reason for the high and low G+C% in these phyla is not clearly understood. But phylogeny specific optimal codon selection has been reported recently (Satapathy et al 2016). Future understanding of translational decoding by the ribosome might explain the phylogeny specific codon usage bias and genome composition.…”
Section: Discussionmentioning
confidence: 99%
“…However, we have observed a lack of correlation between the genome size and genome G+C% in different phylogeny (Supplementary Table 3). It has been reported that the strength of selection on codon usage bias is variable among the bacteria (Sharp et al 2005;Satapathy et al 2012Satapathy et al , 2014Satapathy et al , 2016. In that case bacteria with poor selection on codon usage bias should exhibit low genome G+C%, while bacteria with high genome G+C% must exhibit high selection on codon usage bias.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Synonymous codons in protein-coding genes are not used randomly [1]. The preferential use of synonymous codons per amino acid in highly transcribed genes, often called optimal codons, has been observed in diverse organisms including bacteria, fungi, plants and animals [2][3][4][5][6][7][8][9][10][11][12][13][14], including insects such as flies, mosquitoes, beetles and crickets [10,11,13,15,16]. When optimal codons co-occur with a high count of iso-accepting tRNA gene copies in the genome, which reflects an organism's tRNA abundance [3-5, 12, 17-20], it suggests a history of selection favoring translational optimization [1,3,5,12,13,[20][21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%